Psikoterapi dan Bahasa Bacaan Ruqyah: Studi Analisis Konseptual Hadits dan Medis - Azizah, Milka Ipsi; Rosyana, Devy; Amiruddin, Muhammad; Maulidha, Mutiara (Maliki Interdisciplinary Journal, 2025)
Ruqyah syar’iyyah is a form of alternative therapy in the Islamic tradition which aims to cure physical, psychological and spiritual disorders through reading verses of the Qur’an and prayers in accordance with the guidance of the sharia. This study aims to analyze the validity, legal basis, and effectiveness of ruqyah in the context of Islamic psychotherapy, with an emphasis on the ethics of implementation and the role of ruqyah in treating mental disorders. The research was conducted through a literature study of relevant primary and secondary sources, such as the Qur’an, hadith, as well as scientific articles and previous research results. The results of the study show that ruqyah has a strong legal basis in Islamic teachings as long as it meets certain conditions, such as not containing elements of shirk and using readings that are sourced from the Qur’an and ma’tsur prayers. The validity of ruqyah syar’iyyah in Islam is based on the principles of sharia contained in the Al-Qur’an and hadith. Ruqyah is permissible as long as it does not contain elements of shirk and is carried out in accordance with the teachings taught by the Prophet Muhammad SAW.